(untitled) (Journal of Comparative Social Work, 2009)
In this explorative and comparative article a suitable social distance in the client-social worker relationship will be in focus. When do clients need a social worker “as if she is a friend” and when do they appreciate a professional “as if she is a stranger”? How does context have an impact on what we see as legitimate relationships? We will be listening to voices on these issues from poor single mothers and social workers in five countries – Australia, USA, Canada, Russia and Norway.